2010
DOI: 10.1007/jhep12(2010)027
|View full text |Cite
|
Sign up to set email alerts
|

Cascade supersymmetry breaking and low-scale gauge mediation

Abstract: We propose a new class of models with gauge mediated supersymmetry breaking, the cascade supersymmetry breaking. This class of models is consistent with the gravitino mass as low as O(1) eV without having suppressed gaugino masses, nor the Landau pole problems of the gauge coupling constants of the Standard Model below the scale of the grand unification. In particular, there is no supersymmetric vacuum in the vicinity of the supersymmetry breaking vacuum even for such a low gravitino mass. Thus, the model does… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 104 publications
(175 reference statements)
0
22
0
Order By: Relevance
“…We consider the model of cascade SUSY breaking which was developed in Refs. [19,20]. This model contains a primary SUSY-breaking field Z 0 and a secondary SUSY-breaking field Z 1 , the latter of which will be identified with Z.…”
Section: A Concrete Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…We consider the model of cascade SUSY breaking which was developed in Refs. [19,20]. This model contains a primary SUSY-breaking field Z 0 and a secondary SUSY-breaking field Z 1 , the latter of which will be identified with Z.…”
Section: A Concrete Modelmentioning
confidence: 99%
“…In the following, we take h and κ to be real and positive by rotating the phases of the fields appropriately. We are assuming that the higher dimensional Kähler potential terms are generated radiatively by integrating out certain fields in a generalized O'Raifeartaigh model [19,20]. It can be shown that c 2 0 > 0 when the quartic Z 0 term is perturbatively generated by integrating out fields with R-charges 0 or 2 [21].…”
Section: A Concrete Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, we can obtain sizable gaugino masses in the global minimum of the potential. The models discussed in [9,16,17] with the minimal gauge mediation [18] have the messenger sector separated from the SUSY breaking sector and they have the additional messenger gauge interaction (or the nonrenormalizable interaction in the Kähler potential) between these two sectors. Then, these models do not have a pseudomoduli space in the messenger sector and realize sizable gaugino masses in the global vacuum.…”
Section: The Modelsmentioning
confidence: 99%